Sea sirens - Chu, Amy; Lee, Janet, 1967- (A Trot & Cap'n Bill adventure, 2019)
"Trot, a Vietnamese American surfer girl, and Cap'n Bill, her cranky one-eyed cat, catch too big a wave and wipe out, sucked down into a magical underwater kingdom where an ancient deep-sea battle rages"--